Probing The Data: Perspectives on Race Visibility in Canadian Sentencing Proceedings - Jones, Danardo Sanjay (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2024)
This article analyzes interview data from nine Black criminalized individuals and nine defence lawyers (five white, three Black, and one Arab) about the utility of heightened race visibility in sentencing proceedings. The data reveals a schism between these groups, reflecting different responses to what I refer to as “the paradox of visibility.” For Black people, this paradox occurs when an emphasis on race may simultaneously have a deleterious and ameliorating impact on sentencing. Defence lawyers and judges laud the ameliorative potential of race visibility, which obscures the genuine concern shared by criminalized Black individuals about how they believe their Blackness betrays them in the criminal sentencing context. In this regard, the article explores ethical concerns arising from this paradox. It also argues that race-based strategies at sentencing are not a no-cost or low-cost proposition. Indeed, from the criminalized research participants’ point of view, the cost is not only the risk that an emphasis on race may result in a higher sentence, including longer and harsher custodial sentences, but also an affront to their dignity. In contrast, the defence lawyers strongly supported increased racial visibility to combat what they saw as judicial and prosecutorial intransigence to grapple with race in sentencing proceedings. These perspectives are critical for sentencing judges tasked with sentencing Black individuals and for lawyers who are developing and deploying legal strategies to assist their Black clients.